Orang Muda Katolik sebagai Agen Perubahan Implementasi Gaudium Et Spes dalam Kehidupan Sehari-hari - Teresia Ipo; Teresia Noiman Derung (Jurnal Teologi Injili dan Pendidikan Agama, 2025)
This article examines the role of Catholic Young People (OMK) as agents of change in the context of Gaudium et Spes teachings. In the era of globalization which is marked by the rapid development of technology and materialism, OMK faces challenges in maintaining spiritual and social values. This article analyzes how the teachings of Gaudium et Spes can be a guide for OMK in facing these challenges. Through a literature review and qualitative data analysis, this research shows that OMK has great potential as an agent of change in the Church and society. They can play an active role in promoting social justice, interfaith dialogue and human values. However, to achieve this potential, OMK needs support from various parties, including the Church, family and community. This article concludes that by understanding the teachings of Gaudium et Spes and utilizing their potential, OMK can become a generation that brings hope for the future of the Church and the world.